Inferring habitat use of the Pacific White Shark using vertebral chemistry - Mohan, John A.; Romo-Curiel, Alfonsina E.; Herzka, Sharon Z.; Wells, R. J. David; Miller, Nathan R.; Sosa-Nishizaki, Oscar; García-Rodríguez, Emiliano (Frontiers in Marine Science, 2023)
The conservation and management of highly migratory sharks relies on understanding age-related movements and nursery habitat utilization. We reconstructed the habitat use and migratory history of young White Sharks (Carcharodon carcharias), a highly protected species, by utilizing natural chemical tracers (element:Ca ratios and stable isotope analysis, SIA) in vertebral cartilage growth bands. Two nursery areas in the northeastern Pacific are known, but migration patterns of immature White Sharks within the Gulf of California (GC) and natal philopatry are poorly understood. Vertebrae from coastal Mexican artisanal fisheries off central Baja California in the Pacific (12 neonates and juveniles; 139-280 cm total length) and the GC (3 subadults; 289-355 cm TL) were analyzed to characterize (1) trophic histories from collagen δ13C and δ15N values, and (2) in utero patterns and post-birth environmental histories from element:Ca time-series. Mean δ15N values from vertebral edges of GC sharks, representing the most recent feeding, was +5‰ higher than in the Pacific, reflecting the intense denitrification that permeates the regional food web and supporting SIA as tracers of migration between regions. A subadult from the GC likely resided within the system throughout its life, and two subadults migrated into the GC. Most neonate and juvenile sharks caught in the Pacific had SIA that did not overlap with those of the GC, but a single subadult likely migrated to the GC. Element:Ca ratios displayed ontogenetic trends, with Li:Ca, Zn:Ca, and Ba:Ca significantly higher before the birth mark in sharks captured in the GC. Edge values were significantly higher in Zn:Ca and Ba:Ca in the GC compared to the Pacific, suggesting elemental ratios may serve as tracers of migration between regions. Subadult sharks collected from GC displayed elevated maternal Zn:Ca and Ba:Ca, suggesting mothers may have resided in the GC for an extensive period pre-birth. Some White Sharks may reside within the GC from birth until at least the subadult stage (ca. 3 m TL), and there may be an unidentified nursery. Chemical tracers, coupled with genomic and tagging studies, should improve understanding of the importance of the GC to White Shark populations in the northeast Pacific.